2021
DOI: 10.3389/fmicb.2021.646062
|View full text |Cite
|
Sign up to set email alerts
|

Effector Avr4 in Phytophthora infestans Escapes Host Immunity Mainly Through Early Termination

Abstract: Effector genes play critical roles in the antagonistic interactions between plants and pathogens. However, knowledge of mutation mechanisms and evolutionary processes in effector genes and the contribution of climatic factors to the evolution of effector genes are fragmented but important in sustainable management of plant diseases and securing food supply under changing climates. Here, we used a population genetic approach to explore the evolution of the Avr4 gene in Phytophthora infestans, the causal agent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 79 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…For example, the effector function of P. syringae AvrRpt2 to Arabidopsis RPS2 resistance disappeared when plants were grown for 3 weeks under 28°C ( Wang et al, 2009 ). The strong association of annual mean temperature in the collection sites with nucleotide diversity and/or population differentiation of Avr1 ( Shen et al, 2021 ), Avr2 ( Yang et al, 2020 ), Avr3a ( Yang et al, 2018 ) and Avr4 ( Waheed et al, 2021 ) in P. infestans further supports that local air temperature could influence the evolution of effector genes.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, the effector function of P. syringae AvrRpt2 to Arabidopsis RPS2 resistance disappeared when plants were grown for 3 weeks under 28°C ( Wang et al, 2009 ). The strong association of annual mean temperature in the collection sites with nucleotide diversity and/or population differentiation of Avr1 ( Shen et al, 2021 ), Avr2 ( Yang et al, 2020 ), Avr3a ( Yang et al, 2018 ) and Avr4 ( Waheed et al, 2021 ) in P. infestans further supports that local air temperature could influence the evolution of effector genes.…”
Section: Introductionmentioning
confidence: 65%
“…To maintain these multifaceted functions, effector genes are expected to have a higher evolvability equipped by high genetic variation for quick adaptation to constantly changing biotic and abiotic environments. Indeed, previous studies have reported that the genetic variation in effector genes is higher than many other functional genes in P. infestans and other pathogen species, possibly due to a synergic effect of recombination ( Yang et al, 2018 ; Dale et al, 2019 ), plasticity ( Timilsina et al, 2020 ) and multiple mutation mechanisms including pseudogenization, point mutation, deletion, insertion and truncation ( Shen et al, 2021 ; Waheed et al, 2021 ). The physical locations of many effector genes in the sparse regions of genomes enriching with transposable elements provide unique opportunity for mutations to occur with a minimum fitness penalty to pathogen species ( Haas et al, 2009 ; Dong et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher degree of population differentiation in mtDNA than neutral genome represented by SSR provides further evidence supporting an adaptive evolution (Wu et al, 2016 ; Yang et al, 2018 ; Shen et al, 2021 ; Waheed et al, 2021 ) in the P. infestans molecules. Gene flow is the main evolutionary mechanism determining the population differentiation of species (Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 73%
“…Evolutionary strategies differ largely between conserved genes and other variant genes such as pathogenicity and tissue-specific genes ( Alrefai et al, 2007 ). For example, many housekeeping genes are conserved in evolution due to their essential roles in providing fundamental service to the survival of a cell ( Zhang and Li, 2004 ), whereas many effector genes of pathogens can quickly evolve in responding to host changes ( Waheed et al, 2021 ). Low genetic variation was found in the RAD4 gene studied.…”
Section: Discussionmentioning
confidence: 99%